2021
DOI: 10.3390/cryst11101158
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Bonding of FGH 98 and CoCrNi-Based Medium-Entropy Alloy: Microstructure Evolution and Mechanical Tests

Abstract: The superalloy FGH98 was successfully diffusion bonded (DB) with medium-entropy alloy (MEA) Al3Ti3(CrCoNi)94 using pure Ni as the interlayer at a temperature range of 1050–1170 °C for 1 h under 5 MPa. The microstructure and mechanical properties of joints were investigated. The diffusion bonding seam was composed of an interlayer zone (IZ) and two diffusion-affected zones (DAZ). The IZ and DAZ beside the FGH98 consisted of cubic Ni3(TiAl)-type γ′ phases due to the diffusion of Ti and Al atoms. Meanwhile, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Samiuddin et al (2021), explored the weldability of CoCrNi MEA with SUS 304 stainless steel and concluded that high diffusion bonding temperature embraced defect-free joints which consequently induced maximum shear strength. Du et al (2021) successfully performed diffusion bonding on FGH 98 (Ni-based superalloy) and CoCrNi MEA by utilizing Ni interlayer and achieved maximum shear strength of 592 MPa at 1150 °C (Du et al, 2021). Diffusion bonding on CoCrNi MEA and DD5 (Single crystal Ni-based superalloy) was also executed by Li et al (2021b) The joint received maximum tensile strength (i.e.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Samiuddin et al (2021), explored the weldability of CoCrNi MEA with SUS 304 stainless steel and concluded that high diffusion bonding temperature embraced defect-free joints which consequently induced maximum shear strength. Du et al (2021) successfully performed diffusion bonding on FGH 98 (Ni-based superalloy) and CoCrNi MEA by utilizing Ni interlayer and achieved maximum shear strength of 592 MPa at 1150 °C (Du et al, 2021). Diffusion bonding on CoCrNi MEA and DD5 (Single crystal Ni-based superalloy) was also executed by Li et al (2021b) The joint received maximum tensile strength (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Considering the importance of the two alloys, a joint between the two alloys could be used in the equipment such as reactors, heat exchangers, and piping systems CoCrNi weldments are often used in aerospace components such as turbine blades and engine components, while 304 stainless steel is used in structural components. A joint between the two alloys could be used to connect the structural component to the turbine blade or engine component, providing a strong, corrosion-resistant connection (Bridges et al, 2018;Chai and Tassou, 2020;Du et al, 2021). Nowadays, NGNP (next-generation nuclear power plants) commonly employ thin sheet layers with flow channels, bonded using diffusion bonding, to create plate-type or printed circuit heat exchangers (Southall et al, 2008) for 4th generation Nuclear power plants (Clark et al, 2012a;Clark et al, 2012b;Sah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%